Erfassung eines Delirs bei pädiatrischen Intensivpatienten: Prospektive Studie zur Etablierung des deutschsprachigen CAPD-Scores = Diagnosis of delirium in pediatric intensive care patients : Prospective study to establish the German version of the CAPD - Ritsert, Mona-Lisa; Haken, Rebecca von; Meyburg, Jochen (Monatsschrift Kinderheilkunde, 2016)
BackgroundDelirium in pediatric intensive care patients is usually diagnosed based on nonstandardized clinical evaluation. Recently, the Cornell Assessment of Pediatric Delirium (CAPD), a validated, practical screening tool for the pediatric intensive care unit (PICU), has become available. The aims of this study were to establish a German version of the CAPD and to compare the results of the score with the bedside nurse’s assessment.MethodsAn authorized German version of the CAPD was evaluated in a prospective study on 93 patients (3.5 ± 4.7 [0-17] years) who needed treatment on the PICU following elective surgery. When the patients were awake, the same two trained investigators conducted the CAPD and asked for the bedside nurse’s assessment twice daily in the morning and evening for 5 consecutive days.ResultsA total of 61 patients (65.5 %) were diagnosed with delirium. Half of these patients (n = 31, 33.3 %) had severe delirium and the other half (n = 30, 32.2 %) had milder symptoms for a maximum of 24 h, which could be distinguished from sedative hangover by analysis of the individual test items. Clinical assessment by the bedside nurses deviated significantly from the CAPD results in symptomatic patients, patients with mild delirium, patients on normal wards, and neurologically impaired children.ConclusionsAfter appropriate training, the CAPD can be performed easily and rapidly. Nearly two thirds of all postoperative pediatric intensive care patients develop a mild or severe delirium during their clinical course. Diagnosis of pediatric delirium by clinical evaluation alone is particularly difficult on normal care wards and in patients with mild delirium or neurological impairment.